Earnings Assimilation of Immigrants in Germany: The Importance of Heterogeneity and Attrition Bias - Michael Fertig; Stefanie Schurer (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Heterogeneity in the ethnic composition of Germany's immigrant population renders general conclusions on the degree of economic integration difficult. Using a rich longitudinal data-set, this paper tests for differences in economic assimilation profiles of four entry cohorts of foreign-born immigrants and ethnic Germans. The importance of time-invariant individual unobserved heterogeneity and panel attrition in determining the speed of assimilation is analysed. We find evidence for heterogeneity in the assimilation profiles and for robust assimilation profiles for two entry cohorts only. Omitted variables, systematic sample attrition and the presence of second generation immigrants in the sample influence the speed of assimilation, but do not change the overall picture.
Keywords: I12; C23; 330; Unobserved heterogeneity; panel attrition; sample selection; fixed effects; migration